Evaluating the perception of Mycosis Fungoides patients about their disease before and after educating them - Nasimi, Maryam; Abedini, Robabeh; Fakour, Yousef; Shahabi, Shideh; Kalantari, Yasamin; Etesami, Ifa (Dermatology Practical & Conceptual, 2022)
BACKGROUND:Patient-held beliefs are important for disease management and few studies have evaluated illness perception of Mycosis Fungoides (MF) patients. Here, we aimed to determine the effect of educating MF patients on their perception of their disease. METHODS:Patients with diagnosed MF were asked to fill the Illness Perception Questionnaire-Revised (IPQ-R) once before education and once 3 months later. RESULTS:Fifty-five patients, 41 men and 14 women, with a mean age of 45.5 ± 13.9 years were enrolled. Regarding the main etiologic factor, most patients cited anxiety (91%). After education, the most significant changed belief on disease etiology was immune system dysfunction and the change was twenty-six percent which was observed more in patients with higher educational levels, shorter disease duration, and lower MF stages. Regarding the most prevalent clinical manifestations, the majority of patients mentioned erythema (86%). After education, the greatest change in symptom perception was related to lymphadenopathy (32%) which was significantly associated with less disease duration and those treated with phototherapy. Before education, the mean perception score about the disease chronicity was 23.67 ± 3.549 that increased to 27.71 ± 1.66 (p-value <0.001). This change was more observed in men (p-value=0.03), those with less disease duration, and those treated with phototherapy. CONCLUSION:Generally, MF patients hold favorable perspectives about their disease and educating them positively improves their illness perception. Patients with higher educational levels and lower stages of the disease showed more significant changes in various aspects of illness perception. Hence, early education is recommended in patients with lower educational levels.